ANALYSIS OF VARIOUS FACTORS IN ORDER TO ENHANCE PRODUCTIVITY AND INCOME OF DAIRY CATTLE FARMERS IN CENTRAL JAVA - INDONESIA - Mukson, M.; Isbandi, I.; Santosa, S.I.; Sudjadmogo, S.; Setiadi, A. (Diponegoro University, 2012)
This survey aims were to determine the potency of dairy cattle development, and to find therelationship among of various factors to improve productivity and income of dairy cattle farmers.Semarang, Boyolali and Banyumas districts were taken as study location. Total respondents were 495farmers, in which 225 farmers were members of the Village Unit Cooperative (VUC), 180 farmers weremember of Various Business Cooperative (VBC) and 90 farmers were member of Farmer GroupAssociation (FGA). Primary data were obtained through interviews with farmers and secondary datawere obtained from related institution. Descriptive and Structural Equation Modelling (SEM) analysiswere used in the study. Based on LQ (Location Quotiens) analysis, dairy cattle in Central Java waspotential to be developed. The LQ value of Semarang, Boyolali and Banyumas districs were 4.57, 7.68and 0.46, respectively, with 4.24 on average. The dairy cattle farmer income was IDR 1.024.095/monthwith an average of scale ownership lactation cattle was 2.7 head/farmer. Model Goodness of Fit of SEMwas fit with the SEM requirement. The productivity was influenced significantly (P<0.01) byenvironmental, economic, institutional, and social factors. Dairy cattle farmer income were influencedhighly significant (P<0.01) by technical and institutional factors (P<0.05) of the income. These resultsindicated that the role of technical factors, social, economic, institutional and business environmentneeds to be considered in order to increase business productivity and farmer incomes.